Associations Between Eight Earth Observation‐Derived Climate Variables and Enteropathogen Infection: An Independent Participant Data Meta‐Analysis of Surveillance Studies With Broad Spectrum Nucleic Acid Diagnostics. (5th January 2022) - Colston, Josh M.; Zaitchik, Benjamin F.; Badr, Hamada S.; Burnett, Eleanor; Ali, Syed Asad; Rayamajhi, Ajit; Satter, Syed M.; Eibach, Daniel; Krumkamp, Ralf; May, Jürgen; Chilengi, Roma; Howard, Leigh M.; et al.
Abstract: Diarrheal disease, still a major cause of childhood illness, is caused by numerous, diverse infectious microorganisms, which are differentially sensitive to environmental conditions. Enteropathogen‐specific impacts of climate remain underexplored. Results from 15 studies that diagnosed enteropathogens in 64, 788 stool samples from 20, 760 children in 19 countries were combined. Infection status for 10 common enteropathogens—adenovirus, astrovirus, norovirus, rotavirus, sapovirus, Campylobacter, ETEC, Shigella, Cryptosporidium and Giardia —was matched by date with hydrometeorological variables from a global Earth observation dataset—precipitation and runoff volume, humidity, soil moisture, solar radiation, air pressure, temperature, and wind speed. Models were fitted for each pathogen, accounting for lags, nonlinearity, confounders, and threshold effects. Different variables showed complex, non‐linear associations with infection risk varying in magnitude and direction depending on pathogen species. Rotavirus infection decreased markedly following increasing 7‐day average temperatures—a relative risk of 0.76 (95% confidence interval: 0.69–0.85) above 28°C—while ETEC risk increased by almost half, 1.43 (1.36–1.50), in the 20–35°C range. Risk for all pathogens was highest following soil moistures in the upper range. Humidity was associated with increases in bacterial infections and decreases in most viral infections. Several virus species' risk increased following lower‐than‐average rainfall, while rotavirus and ETEC increased with heavier runoff. Temperature, soil moisture, and humidity are particularly influential parameters across all enteropathogens, likely impacting pathogen survival outside the host. Precipitation and runoff have divergent associations with different enteric viruses. These effects may engender shifts in the relative burden of diarrhea‐causing agents as the global climate changes. Plain Language Summary: Diarrheal disease is a big health problem for children. It can be caused by different bugs, which can be caught more easily in certain weather conditions, though not much is understood about this because the climate varies so much from one place to the next. This study combined data from many different countries where diarrhea‐causing bugs were diagnosed in children's stool. Satellites recorded what the weather was like on the day each sample was collected. Rotavirus is easiest to catch in cold weather and when water washes over the ground after rain. Dry weather also makes it and other viruses easy to catch. Bacteria spread best when the air is warm and humid, and the soil moist, though one type of E. coli can also be spread in rainwater. Climate change will make dry places drier, wet places wetter and everywhere warmer. This might lead to more diarrhea caused by bacteria and less by viruses in some places, though places with moist soil might see more of every kind of bug. Key Points: Many pathogens cause diarrhea in children and are affected in different ways by weather conditions like rainfall, temperature, and humidity Diarrhea‐causing bacteria infections increase in warm, humid weather and when soil is moist, though ETEC is sensitive to rainfall extremes High humidity decreases prevalence of several viruses, though only rotavirus increases in cold weather and following heavy surface runoff